4.9k views
5 votes
What is the answer to -4-3x=6x-6

User ERadical
by
5.1k points

2 Answers

4 votes

Answer:

x = 2/9

Explanation:

First, move and combine like-terms. Then, caluculate the sum. Then divide both sides by 9.

User KernelPanik
by
5.1k points
1 vote

x=2/9

Explanation:

Step 1: Simplify both sides of the equation.

−4−3x=6x−6

−4+−3x=6x+−6

−3x−4=6x−6

Step 2: Subtract 6x from both sides.

−3x−4−6x=6x−6−6x

−9x−4=−6

Step 3: Add 4 to both sides.

−9x−4+4=−6+4

−9x=−2

Step 4: Divide both sides by -9.

−9x

−9

=

−2

−9

User Mrz
by
5.1k points